The role of international investment agreements in attracting foreign direct investment to developing countries (UN New YorkUS, 2009)
Provides a brief overview of the overall determinants for FDI and focuses on the role of IIAs as FDI determinants. Reviews a number of existing econometric studies on the impact of IIAs on FDI inflows into developing countries.
Keywords: FOREIGN INVESTMENT